Persistent Conventions in 20th Century Architecture Photography - david Alarcón; Patricia Méndez (Materia Arquitectura)
Photography and architecture maintain a unique and constant relationship with each other. The invention and technology of one proved to be the optimal mechanisms for the dissemination of the latter, transforming it into an ideal model in front of a camera. However, these evidences, embodied in paper, also reveal the installation of a disciplinary field that tied the visual and aesthetic canons of both disciplines. This text proposes therefore to investigate this binomial based on the invariants that circumscribed the architecture photography of the 20th Century. The methodology applied resorted to texts that delve into visual culture, together with theoretical literature about photography and classic examples of architecture. In the attempt to analyze, partially, the visual communication of the architecture – from a contemporary perspective, overvalued by image consumerism – it is concluded that it is evident that the photographer officiates as the translator of architectural conventions, while the architect does it as an organizer of his images. Both establish visual  codes that last over time and, in each photographic act, confirm and deepen their disciplinary artistic discourses.